Design of Split-Hopkinson Pressure Bar Specimen Fixture to Accommodate Punch and Double-Notch Shear Testing - Arya Dipajaya; Kemal I. Ahmad; Muhammad A. Kariem (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
This study focused on the design of a specimen fixture which can be installed on the end of a conventional transmission bar so that shear testing (punch and double-notch) can be conducted with any conventional split-Hopkinson apparatus. The research was conducted by using the finite element method in Abaqus/CAE with 6061-T651 Aluminum as the specimen material. The research successfully determined the effect of the fixture’s geometry and dimensions on the split-Hopkinson shear bar testing results. The optimum double-notch fixture provides great accuracy, having only a shear stress value difference of 1.49% with the original setup, while attaining force equilibrium after only 70 μs. The punch fixture, however, could only reach force equilibrium after 100 μs, thus providing too few observable data. Future work on the punch fixture is needed.